A Hybridized Finite Taylor Formula by Fluctuation Free Remainder Term for a Multivariable Function Approximation - (:unkn) unknown (My University, 2009)
Based on the Taylor's Theorem for functions of several variables, a new formulation is developed here to approximate the remainder term of the Multivariate Taylor polynomial by means of the recently developed Fluctuation Theorem. This new formulation is tested on functions of two variables. © 2009 American Institute of Physics.
Keywords: Approximation Methods; Explicit Remainder Term; Fluctuation Expansion; Multivariate Taylor's Theorem